2005
DOI: 10.1080/09674845.2005.11732688
|View full text |Cite
|
Sign up to set email alerts
|

Embryopathy in experimental diabetic gestation: assessment of oxidative stress and antioxidant defence

Abstract: Maternal diabetes is associated with an increased rate of congenital fetal anomaly. In the present study, diabetes was induced by streptozotocin in female rats one week prior to conception and the embryos were examined during organogenesis. Experimental diabetes is associated with over-production of free radicals and disturbed antioxidant defence, particularly in malformed embryos. Oxidative stress is demonstrated by increased MDA accumulation and reduced glutathione levels. Despite large differences in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 26 publications
3
15
0
1
Order By: Relevance
“…The elevated levels of PGFM in the malformed fetuses of both diabetic groups reported in the present study may reflect oxidative stress status, as has been suggested by El-Bassiouni et al [42]. Yin et al [43] suggested that PGF 2 α in humans is derived from the isoprostane pathways, which are PG-like compounds formed in vivo from the free radical-catalysed peroxidation of arachidonic acid without the activity of COX enzyme, an alternative route for the formation of PGF 2 α in vivo .…”
Section: Discussionsupporting
confidence: 76%
“…The elevated levels of PGFM in the malformed fetuses of both diabetic groups reported in the present study may reflect oxidative stress status, as has been suggested by El-Bassiouni et al [42]. Yin et al [43] suggested that PGF 2 α in humans is derived from the isoprostane pathways, which are PG-like compounds formed in vivo from the free radical-catalysed peroxidation of arachidonic acid without the activity of COX enzyme, an alternative route for the formation of PGF 2 α in vivo .…”
Section: Discussionsupporting
confidence: 76%
“…The effects of this imbalance are difficult to predict especially in the second half of pregnancy. During organogenesis, oxidative stress was implicated in occurrence of fetal malformations in diabetic mothers [17] . The antioxidant capacity of rat embryo was reported to gradually increase with gestational age [18] .…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) can also alter the embryonic development and lead to early embryo death (6)(7)(8). In this respect, diabetes, a condition characterized by high blood glucose concentrations, represents a model of oxidative stress related to embryo toxicity (9). We have recently described that the IVF therapy leading to the ovarian stimulation produces a disturbance in the oxidant-antioxidant balance, causing the serum to be less protected against oxidation (10).…”
mentioning
confidence: 98%